Neuroprotective Effect of Bacopa Monnieri Extract on Oxidized Low Density Lipoprotein-Induced Neurotoxicity in SH-SY5Y Neuroblastoma Cells - Yamchuen, Panit; Chaiwiang, Narttaya; Lapphanichayakool, Phakhamon; Ingkaninan, Kornkanok; Limpeanchob, Nanteetip (Journal of Basic and Applied Pharmacology, 2017)
Oxidized low density lipoprotein (LDL)-mediates neurotoxicity and possibly plays some roles in the pathological process of Alzheimer’s disease (AD). Neuroprotection of Bacapa monerri (L.) Wettst (BM) has been studied in various cells and animal models but not in oxidized LDL-induced toxicity. This study aimed to investigate the neuroprotective effects of BM extract and fourcomponents including three bacoside A; bacopaside I (BA-I), II (Ba-II), and bacoside A3 (Ba-A3), and one flavonoid; luteolin (Lut) in SH-SY5Y neuroblastoma cells. The results demonstrated that BM extract diminished the neurotoxicity of oxidized LDL in a dose dependent manner, potentially by suppression of cellular oxidative stress. Among four tested compounds, Lut exhibited the most effect on preventing the cell injury mediated by oxidized LDL. These compounds also suppressed the increment of cellular acetylcholinesterase (AChE) activity mediated by oxidized LDL, possibly as the consequence of oxidation suppression. These data support the beneficial effect of BM as a neuroprotective agent and this effect is possibly a combined result of its constituents.